The Effect of Greenhouse and Biopore on Community Development of Economy and Knowledge of Citeureup Village During the Pandemic - Tania Verasta; Ihsan Maulidin; Hapsah Aulia Azzahra; Aulya Sholehah Wataawa Sau Bhis Sobri; Amaliyah Rohsari Indah Utami (Journal of Innovation and Community Engagement, 2021)
Citeureup Village, RW 06, located in Bandung Regency, West Java Province, is a regional area with low-level economy. The Covid-19 pandemic has made it worse and adding difficulties to the villagers. On the other hand, this area also often experiences flooding with an erratic pattern. Therefore, efforts are needed to improve local food security, economy, and flood disaster mitigation for the Citeureup Village community. Efforts has been made by Telkom University, some through activities carried out by students of the Undergraduate Program in Engineering Physics (TF), which were to carry out community service activities funded by the Village Development and Empowerment Holistic Program (PHP2D) in 2020. These activities were decided by decree number 29/E2/KM/2020. The results of these activities are the construction of a Hydroponic Greenhouse (HG) on ??10m x 4m and biopore infiltration holes as many as 45 hole constructions throughout RW 06 Citeureup Village. Three months after construction, HG's existence has succeeded in improving Citeureup Villagers behavior and practical knowledge in hydroponic and biopore systems from 21% to 98%. As conclusion, Telkom University has succeeded in playing role in improving knowledge, local food security, economy, and reducing flood inundation at Citereup Village.